Pengaruh Fitur Instagram Stories Terhadap Eksistensi Diri Remaja (Survei Pada Remaja Di RW 09 Ciledug, Kelurahan Sudimara Tangerang) - Sinambela, Bertha K.; Zevi Ariska (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2023)
Social media is in great demand and is becoming a trend, especially among teenagers. The development of social media that is so significant makes this media a place for self-existence, one of which is the Instagram stories feature. This study uses the uses and gratification theory, where this theory focuses on the use of media to satisfy one's needs. This study uses a positivistic paradigm, a quantitative approach, with a survey method and the research is explanatory. The population of 207 respondents took a sample using the Slovin formula with a precision of 5%, resulting in a sample of 136 respondents. The results of the study prove that the influence of the Instagram stories feature has an effect on the self-existence of adolescents due to the influence of the independent variable (independent) which has a t count of 9,170 > 1,977 with a significance value of 0.000 < 0.05. So it can be concluded, namely accepting Ha and rejecting Ho, meaning that the Instagram Stories feature variable has a significant influence on Adolescent Self-Existence